Scleral remodelling in myopia and its manipulation: a review of recent advances in scleral strengthening and myopia control - Backhouse, Simon; Gentle, Alex (Annals of Eye Science, 2018)
The biological mechanisms of eye growth and refractive development are increasingly well characterised, a result of many careful studies that have been carried out over many years. As the outer coat of the eye, the sclera has the ultimate impact on the restraint or facilitation of eye growth, thus any changes in its biochemistry, ultrastructure, gross morphology and/or biomechanical properties are critical in refractive error development and, in particular, the development of myopia. The current review briefly revisits our basic understanding of the structure and biomechanics of the sclera and how these are regulated and modified during eye growth and myopia development. The review then applies this knowledge in considering recent advances in our understanding of how the mechanisms of scleral remodelling may be manipulated or controlled, in order to constrain eye growth and limit the development of myopia, in particular the higher degrees of myopia that lead to vision loss and blindness. In doing so, the review specifically considers recent approaches to the strengthening of the sclera, through collagen cross-linking, scleral transplantation, implantation or injection of biomaterials, or the direct therapeutic targeting and manipulation of the biochemical mechanisms known to be involved in myopia development. These latest approaches to the control of scleral changes in myopia are, where possible, placed in the context of our understanding of scleral biology, in order to bring a more complete understanding of current and future therapeutic interventions in myopia, and their consequences.